PEMBERIAN HAK ASUH BERSAMA DALAM PENYELESAIAN SENGKETA HAK ASUH ANAK DI INDONESIA: PERSPEKTIF MASLAHAH MURSALAH - Maulana, Moh. Iqbal Rifki; Safitri, Melani Intan (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
In general, looking at the various existing regulations and practices in court decisions, child custody law in Indonesia still provides sole custody in resolving child custody disputes. However, in recent years, several judges have begun to establish joint custody in child custody disputes. The main data in this study is in the form of five Religious Court rulings on joint child custody. The purpose of this study is to reveal the judge's legal considerations in determining joint custody and in what cases child custody should be applied from the perspective of maslahah mursalah. This research uses qualitative methods with a normative juridical approach. The result of this study is that the judge's consideration in determining joint custody is not based on the KHI, but based on the best interests of the child which is the judge's interpretation of Article 14 paragraph (1) of Law Number 35 of 2014 concerning Child Protection. Before determining child custody, the judge must first look at the track record of both parents, if both are good in nature and have the ability to take care of children, then the judge can consider determining child custody together. If one parent behaves badly and does not have the ability to care for the child, then it is better to establish sole custody solely in the best interest of the child based on the maslahah mursalah.